Associação entre alterações cognitivas e comportamentais com processos inflamatórios e neuroquímicos em modelo experimental de Malária - Aline Silva de Miranda (2011)
Malaria is the main and most serious parasitic disease of mankind. Cerebral Malaria (CM) has been defined as a potentially reversible diffuse encephalopathy characterized mainly by coma and the presence of asexual forms of P. falciparum parasites in peripheral blood smears in the absence of other causes of encephalopathy.This condition presents a complex and incompletely understood pathogenesis, in which vascular, immunological and metabolic changes have been described. In the present work were investigated possible associations between cognitive and behavioral alterations and neurochemical and inflammatory processes in the CNS using thePlasmodium berghei ANKA (PbA) model of CM. Female C57BL/6 mice were infected with PbA by the intraperitoneal route (i.p), using a standardized inoculation of 106 parasitized red blood cells. Significant neurological and behavioral changes, as assessed by the SHIRPA battery, were found on day 6 post- infection. In parallel to thealterations found in the functional domains of the SHIRPA battery, were observed a significant increase of glutamate release in the cerebral cortex and of glutamate levels in the cerebrospinal fluid of infected mice, as measured by a spectrofluorimeter. Furthermore, CM mice presented high levels of anxiety on day 5 post-infection, as indicated by the significant decrease in the percentage of time spent on and in thenumber of entries made onto the open arms of the elevated plus maze. In association with the anxiety symptoms were observed histopathological changes in different brain regions, particularly in the CA1 region of hippocampus, and a significant increase of proinflammatory cytokine levels (IL-1 and TNF-) in the brain tissue of infected mice,as assessed by ELISA technique. Thus, our results suggest that glutamate may play an important role in the pathogenesis of CM and that the exacerbated production of proinflammatory cytokines in the CNS, especially IL-1 and TNF-, during the infection, could contribute significantly to the development of the behavioral alterationsobserved in CM mice.